Modified photoanode based on zinc oxide nanorods for photoelectrochemical water splitting - Wei, Yuefan. (2013)
Among the rich variety of photoelectrode materials, zinc oxide (ZnO) is one of the most promising candidates due to its high electrochemical stability, suitable conduction/valence band edges, high electron mobility and lower recombination of electrons and holes. However, the relatively low photocurrent density and low photocurrent-hydrogen conversion efficiency of ZnO largely limit its practical application in water splitting. This work aims to improve the photoelectrochemical (PEC) properties of ZnO-based photoelectrode from two aspects: substrate modification and ZnO functionalization. On substrate modification, two kinds of substrates had been modified. Firstly, ZnO nanorod arrays were prepared on a V-grooved silicon (Si) substrate and used as the photoanode of PEC cell. The light trapping and overall PEC cell performance were greatly enhanced. Secondly, ZnO nanorods grown on polyethylene terephthalate (PET) flexible substrate were used as the photoanode. The effects of plasmonic enhanced absorption, surface recombination inhibition and improved charge transport were investigated and further optimized by varying the silver (Ag) thickness and the curvature of the PET substrates. On functionalization ZnO nanorods, firstly, multi-walled carbon nanotubes (MWCNTs) were introduced to improve the PEC cell performance. Secondly, Ag nanoparticles were used to decorate ZnO nanorods with the assistance of polydopamine. Modified photoelectrode achieves excellent light harvesting and charge-carriers transportation. All designed modifications were potential strategies to realize the practical use of ZnO as photoelectrode material.